Phytoremediation capacity of heavy metals in emerging native plant species in mining liabilities of Sinchao-Peru. - Walter-Villegas, L. (2022)
We determined the species of wild herbaceous flora with phytoremediation capacity in the area of Sinchao mining liabilities, located in the district of Chugur, Province of Hualgayoc, where we conducted the analysis of the concentration of metals in the species Calamagrostis tarmensis, Paspalum bonplandianum, Carex pichinchensis, Lachemilla orbiculata and Juncus conglomeratus selected for their high importance in the area, Lachemilla orbiculata and Juncus conglomeratus, selected for their high importance in the area. Subsequently, the Translocation Factor and Bioconcentration Factor were calculated, which indicated whether the plant is a phytostabilizer or phytoextractor of aluminum, arsenic, lead, chromium, copper, cadmium, magnesium, manganese, zinc, strontium, antimony, thallium, iron, mercury, nickel and tin. The research identified that the species Paspalum bonplandianum accumulates the highest amount of metals (mg/kg), such as aluminum (2844.6), mercury (0.3), antimony (13), tin (1.4), zinc (760.2), chromium (3.86) and nickel (3.59). Likewise, the highest concentration of heavy metals is stored in the root part of all species, with the exception of Lachemilla orbiculata which is stored in the aerial part. Finally, by means of the translocation factors (TF) a nd bioconcentration factors (BCF) it was established that the species Calamagrostis tarmensis, Paspalum bonplandianum, Carex pichinchensis, Lachemilla orbiculata and Juncus conglomeratus would be phytoextractive species of Mg and Mn; likewise, Lachemilla orbiculata would also be phytoextractive of Sr and Zn. On the other hand, Calamagrostis tarmensis could be applied in phytostabilization techniques for Ti, as well as Paspalum bonplandianum for Sb, Zn and Cr, the species Carex pichinchensis for Zn, the species Lachemilla orbiculata for Cd and Mn and fina lly Juncus conglomeratus for Cd, Cr and Zn.